Evaluation of the Role of Serum Malondialdehyde in the Pathogenesis of Diabetic Retinopathy - Hassan , Zena M.; Hamdi , Rana A.; Al Bassam, Ebtehal N. (Journal of the Faculty of Medicine Baghdad, 2022)
Background:  The most typical consequence of diabetes mellitus is diabetic retinopathy. An important part of the etiology of diabetes and diabetic retinopathy is played by oxidative stress. Malondialdehyde is a dialdehyde that is moderately toxic and is frequently used as a marker for oxidative stress as well as lipid peroxidation.                     Objectives: To assess the serum malondialdehyde levels in diabetic patients with and those without retinopathy and to compare these levels to controls .In additions to, investigate the relationship between serum malondialdehyde level and long glycemic control, the glycated hemoglobin (HbA1c).Patients and Methods: This case-control study included (120) individuals from 40 to 70 years of age. They were divided into three groups: Group 1: 40 type 2diabetic patients with retinopathy, Group 2 :40 type 2 diabetic patients without retinopathy, and Group 3 40 controls .The biochemical testes included fasting blood glucose measured by Cobas c 311 systems, glycated hemoglobinHbA1c measured by Cobas c 111 systems, and serum malondialdehyde (MDA) measured by enzyme linked immunosorbent assay (ELISA).Results: A higer mean value of (MDA) was found serum diabetic patients with and without retinopathy as compared to control (p=0.0001). As well as a significantly higher mean value of serum (MDA)  in diabetic patients with retinopathy as compared to those without (p=0.0001).A significant positive correlation was found between serum(MDA)  and HbA1C in diabetic patient with retinopathy group (r=0.931,p=0.0001) .Conclusion: Higher serum levels of malondialdehyde is an indicator of increased lipid peroxidation that may be involved in pathogeneses of retinopathy in uncontrolled type 2 diabetic patients.